2020
DOI: 10.1530/eje-20-0131
|View full text |Cite
|
Sign up to set email alerts
|

Detailed characterization of metastatic lymph nodes improves the prediction accuracy of currently used risk stratification systems in N1 stage papillary thyroid cancer

Abstract: Objective The characteristics of metastatic lymph nodes (MLNs) have been investigated as important predictors of recurrence and progression in papillary thyroid cancer (PTC). However, clinically applicable risk stratification systems are limited to the assessment of size and number of MLNs. This study investigated the predictive value of detailed characteristics of MLNs in combination with currently used risk stratification systems. Design and methods We retrospectively characterized 2811 MLNs from 9014 harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Previous studies have found that low ratio of metastatic LNs predicted a low risk of recurrence and better disease-specific survival [31][32][33]. In our study, patients in the HT group had lower TNM stages and number and ratio of metastasis LNs.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have found that low ratio of metastatic LNs predicted a low risk of recurrence and better disease-specific survival [31][32][33]. In our study, patients in the HT group had lower TNM stages and number and ratio of metastasis LNs.…”
Section: Discussionsupporting
confidence: 57%
“…LNM of PTC occurs in a stepwise fashion. Spreading from the thyroid gland, the central and lateral lymph node compartments on the ipsilateral side of the thyroid tumor represent the first echelons of lymphatic drainage, followed by the mediastinal and contralateral lateral lymph node compartments ( 13 , 14 ). In a previous study, our team found that the region of PTC LNM was significantly associated with the location of the primary tumor ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a new approach called active surveillance is being widely studied in the clinical setting [4]. However, basic experiments and clinical studies on thyroid cancer occurring in young patients and refractory thyroid cancer relatively commonly observed in the elderly are also being conducted [5][6][7][8]. These efforts have led to the development of various tyrosine kinase inhibitors, including targeted therapy for BRAFV600E, for the clinical setting.…”
Section: Introductionmentioning
confidence: 99%